2020
DOI: 10.1590/1414-431x20207851
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil activity in sepsis: a systematic review

Abstract: The neutrophil is an important cell in host defense against infections, acting as the first line of microorganism control. However, this cell exhibits dysregulated activity in sepsis and may contribute to the pathogenesis of the disease. This systematic review aimed to highlight the major scientific findings regarding neutrophil activity in sepsis reported in clinical and experimental research published in the last 10 years. The search was conducted in the Virtual Health Library of PAHO-WHO (BVS) and PubMed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(50 reference statements)
0
7
0
2
Order By: Relevance
“…Under physiological conditions, neutrophils undergo apoptosis to maintain their homeostasis. However, during sepsis, neutrophils undergo several functional alterations, including reduced migration, altered antimicrobial activity, and delayed apoptosis, contributing to immune dysfunction and persistent inflammation [39,40]. Altogether, neutrophil alterations contribute to the worsening of sepsis and the development of secondary complications.…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, neutrophils undergo apoptosis to maintain their homeostasis. However, during sepsis, neutrophils undergo several functional alterations, including reduced migration, altered antimicrobial activity, and delayed apoptosis, contributing to immune dysfunction and persistent inflammation [39,40]. Altogether, neutrophil alterations contribute to the worsening of sepsis and the development of secondary complications.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Platelet indices include the platelet distribution width (PDW), which is a measure of platelet anisocytosis, which, accordingly, increases during accelerated platelet turnover; the mean platelet volume (MPV), which is an indicator of platelet size; and plateletcrit, a measure of total platelet mass. Some authors showed that platelet indices are reliable prognostic biomarkers of sepsis, whereas others found the opposite [39,96,98]. To date, there are few studies to draw a conclusion on the potential role of platelet indices as biomarkers of sepsis.…”
Section: Plateletsmentioning
confidence: 99%
“…Nevertheless, comprehensive approaches that profile the immune response more holistically in sepsis patients are still lacking 7,47,48 . Specifically, the functional impact of different neutrophil subsets in sepsis is not completely understood 46,49 .…”
Section: Discussionmentioning
confidence: 99%
“…LPS вызывает ингибирование апоптоза нейтрофилов при бактериальной инфекции (грамотрицательный сепсис), сахарном диабете, сердечно-сосудистых, нейродегенеративных заболеваниях [7]. Под действием LPS в нейтрофилах увеличивается продукция АФК, провоспалительных цитокинов и различных медиаторов воспаления [8].…”
Section: Abstract: Chronic Heart Failure Endotoxemia Neutrophils Apop...unclassified
“…Действие LPS, помимо продуцирования АФК, вызывает синтез различных провоспалительных цитокинов [5,7]. Наши исследования функциональных свойств нейтрофилов больных с ХСН показали, что в данном случае наблюдается увеличение продукции провоспалительных цитокинов (по сравнению с нейтрофилами контрольной группы): TNFα, IL-1b, IL-6 (рис.…”
Section: результаты исследования и их обсуждениеunclassified